2009
DOI: 10.1099/vir.0.008912-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral ubiquitin ligase WSSV222 is required for efficient white spot syndrome virus replication in shrimp

Abstract: The E3 ligase WSSV222 of white spot syndrome virus (WSSV) is involved in anti-apoptosis regulation by ubiquitin-mediated degradation of tumour suppressor-like protein (TSL), a shrimp tumour suppressor. In the present study, WSSV222 gene expression was silenced by using specific small interfering RNA (siRNA) in Sf9 and BHK cells. Based on the results of the in vitro silencing, WSSV-challenged shrimp were treated with anti-WSSV222 siRNA to knock down WSSV222 protein expression. The survival rate of shrimp and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Therefore, we performed the ubiquitination assay in vitro and in S2 cells. Both results showed that FcUbc could ubiquitinate WRD2 and WRD3 of WSSV277 and WSSV304, two of the four WSSV RING domain-containing proteins that have been reported to play a great part in WSSV pathogenesis (12,14,31). Although WRD1 and WRD4 of WSSV254 and WSSV462 were not ubiquitinated by FcUbc, FcUbc could possibly interact with them in other ways, and such proteins' interaction in vivo may also contribute to anti-WSSV response.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, we performed the ubiquitination assay in vitro and in S2 cells. Both results showed that FcUbc could ubiquitinate WRD2 and WRD3 of WSSV277 and WSSV304, two of the four WSSV RING domain-containing proteins that have been reported to play a great part in WSSV pathogenesis (12,14,31). Although WRD1 and WRD4 of WSSV254 and WSSV462 were not ubiquitinated by FcUbc, FcUbc could possibly interact with them in other ways, and such proteins' interaction in vivo may also contribute to anti-WSSV response.…”
Section: Discussionmentioning
confidence: 80%
“…AAL89330.1), contain the RING-H2 motifs and may function as the E3 ligases (31). The E3 ligase activity of WSSV277 is involved in regulation of antiapoptosis by ubiquitin-mediated degradation of tumor suppressor-like (TSL) protein (12), and it is required for efficient WSSV replication (14). WSSV304 serves as a ubiquitin ligase E3 to sequester a shrimp ubiquitin-conjugating enzyme, Penaeus vannamei Ubc (PvUbc), for viral pathogenesis (31).…”
mentioning
confidence: 99%
“…When the titre was measured by quantitative PCR, the viral titre was reduced twofold to 1 log reduction. RNAi targeting the viral ubiquitin ligase WSSV222, an anti-apoptosis protein of WSSV dropped the titre 20 fold from 2.6 9 10 7 to 1.3 9 10 6 [62]. RNAi against the capsid gene of PmergDNV reduced the titre from 3.4 9 10 3 to 3.6 9 10 2 [93].…”
Section: Effects On Viral Titrementioning
confidence: 99%
“…In almost all cases reported, survival increased following the administration of dsRNA, triggering of the RNAi pathway. RNAi has down regulated White Spot Syndrome Virus and allowed a 85 % reduction in mortality when targeting the VP28 envelope gene, suggested to play a role in WSSV infection [114,148]; 78 % reduction in mortality when targeting RR2 ribonucleotide reductase; 70 % reduction in mortality against VP19 envelope gene [154]; 47 % reduction in mortality against viral ubiquitin ligase [62]; 44 % reduction in mortality when antagonistic to the DNA polymerase. Similarly, when yellow head virus was down regulated by attacking its protease gene and a host host Rab7 GTPase, mortality was reduced by 90 % [143].…”
Section: Rnai With Special Reference To Controlling Viruses In Crustaceamentioning
confidence: 99%
“…For example, adenovirus cannot replicate its genome if proteasome activity is inhibited (8). It has already been shown that WSSV encodes ubiquitin ligase (E3) and that this is required for WSSV pathogenesis and replication (14,38). This suggests that proteasome ␣4 might also be required for WSSV replication, and if so, then the dsRNA suppression of proteasome ␣4 at 25°C would account for the observed reduction in WSSV copy number.…”
Section: Discussionmentioning
confidence: 99%